Practical-Based Culinary Education to Develop Vocational Skills for Deaf Students at SLBN Cicendo - Febianty Diane Suherman; Imas Diana Aprilia; Juhanaini Juhanaini; Budi Susetyo; Iding Tarsidi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
Vocational education plays a critical role in preparing deaf students for successful participation in employment and independent living. However, vocational programs in special schools often emphasize technical instruction without adequately connecting learning experiences to outcomes in the school-to-work transition. This study aimed to examine how practice-based culinary learning contributes to the development of vocational competence and transition readiness among deaf students from a Life Centered Career Education (LCCE) perspective. A qualitative implementative case study was conducted at SLBN Cicendo involving deaf students and vocational teachers participating in a culinary training program. Data were collected through participant observation, semi-structured interviews, documentation, and performance-based assessment, and were analyzed using interactive and thematic analysis. The findings revealed that practice-based culinary learning strengthened students’ procedural competence, work accuracy, task responsibility, independence, and adaptive work behaviors through authentic and visually supported learning experiences. Repeated hands-on activities enabled students to internalize workplace routines and develop employability-related skills, including discipline, collaboration, and persistence. From an LCCE perspective, the learning process functioned not only as vocational training but also as a structured school-to-work transition mechanism that connected technical competence with daily living and occupational skills. This study contributes to special education literature by demonstrating how experiential vocational learning can operationalize LCCE principles in deaf education and support transition-oriented instructional practices. The findings offer practical implications for developing vocational curricula and transition programs that better prepare deaf students for inclusive employment opportunities.